2015
DOI: 10.1111/mmi.13029
|View full text |Cite
|
Sign up to set email alerts
|

A new quorum‐sensing system (TprA/PhrA) for Streptococcus pneumoniaeD39 that regulates a lantibiotic biosynthesis gene cluster

Abstract: The Phr peptides of Bacillus species mediate quorum sensing, but their identification and function in other species of bacteria has not been determined. We have identified a Phr peptide quorum sensing system (TprA/PhrA) that controls the expression of a lantibiotic gene cluster in the Gram-positive human pathogen, Streptococcus pneumoniae. Lantibiotics are highly modified peptides that are part of the bacteriocin family of antimicrobial peptides. We have characterized the basic mechanism for a Phr peptide sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 83 publications
(127 reference statements)
2
103
0
Order By: Relevance
“…Production of mutacin I, the Bifidobacterium longum DJO10A lantibiotic and the two component haloduracin from Bacillus halodurans was also only seen on solid media [66,68,69], and it has been proposed that the dense colonization necessary for mutacin I production is reminiscent of a biofilm condition [66]. A putative lantibiotic cluster in Streptococcus pneumoniae has recently been shown to be controlled by quorum sensing, with expression being induced at high cell densities and depending on the carbon source [70]. Alternatively, the mechanism of trypsin may rely on pre-peptide cleavage rather than induction; in vitro biosynthesis of nisin using just nisABC successfully produced active nisin after treatment with trypsin [49].…”
Section: Discussionmentioning
confidence: 99%
“…Production of mutacin I, the Bifidobacterium longum DJO10A lantibiotic and the two component haloduracin from Bacillus halodurans was also only seen on solid media [66,68,69], and it has been proposed that the dense colonization necessary for mutacin I production is reminiscent of a biofilm condition [66]. A putative lantibiotic cluster in Streptococcus pneumoniae has recently been shown to be controlled by quorum sensing, with expression being induced at high cell densities and depending on the carbon source [70]. Alternatively, the mechanism of trypsin may rely on pre-peptide cleavage rather than induction; in vitro biosynthesis of nisin using just nisABC successfully produced active nisin after treatment with trypsin [49].…”
Section: Discussionmentioning
confidence: 99%
“…QS systems often regulate the production of extracellular products (13), such as antibiotics (14,15) and proteases (28). One hypothesis is that this regulation prevents these products from being produced at low cell densities, when the fitness cost for each individual bacterium may outweigh any benefit of the small amount of produced good (12).…”
Section: Discussionmentioning
confidence: 99%
“…These signal molecules are bound by members of the LuxR family of transcription factors, which control gene expression in an AHL concentration-dependent manner. In many cases, AHLs control the production of extracellular factors, including proteases and antibiotics, which may allow resources to be dedicated to these metabolically expensive products solely under conditions in which the bacterial species has reached a sufficient density to impact its surrounding environment (13)(14)(15).…”
mentioning
confidence: 99%
“…More recent studies have revealed a distinct signal transduction architecture, where an active form of a secreted peptide is internalized into cells and directly binds a transcription factor from the RRNPP (Rap, Rgg, NprR, PlcR and PrgX) superfamily (Rocha‐Estrada et al ., ). There are multiple RRNPP systems encoded in the pneumococcal pangenome (Bortoni et al ., ; Hoover et al ., ; Kadam et al ., ), and cognate peptides have been identified for two of the regulators (PhrA for TprA and PhrA2 for TprA2) (Hoover et al ., ; Kadam et al ., ). Thus, pneumococcal strains make use of distinct peptide‐induced signal transduction pathways during infection.…”
Section: Introductionmentioning
confidence: 99%